ANALISIS WACANA KRITIS IKLAN ROKOK DJARUM 76 - Atikah Nurul Asdah; Jufri Jufri; Syamsudduha Syamsudduha (Universitas Negeri Makassar, 2020)
Critical Discourse Analysis of Djarum Cigarettes 76. This study aims to determine the form of choice of words and the meaning of the references contained in the choice of Indonesian language discourse in the Djarum 76 cigarette ad edition